Role of the pharmacist in improving inhaler technique and asthma management in rural areas in Jordan - Basheti IA; Salhi YB; Basheti MM; Hamadi SA; Al-Qerem W (Dove Medical Press, 2019)
Iman A Basheti,1 Yara B Salhi,1 Mariam M Basheti,2 Salim A Hamadi,3 Walid Al-Qerem41Department of Clinical Pharmacy and Therapeutics, Faculty of Pharmacy, Applied Science Private University, Amman, Jordan; 2Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Pharmacology & Biomedical Sciences, Faculty of Pharmacy and Medical Sciences, Petra University, Amman, Jordan; 4Department of Pharmacy, Al-Zaytoonah University of Jordan, College of Pharmacy, Amman, JordanIntroduction: Pharmacists can have a valuable role in educating patients on correct inhaler technique leading to improved asthma management. Rural areas can benefit from the role of the pharmacist considering the barriers found in attending primary health-care facilities.Objectives: This study aimed to assess the impact of inhaler technique education delivered by pharmacists on patients’ inhaler technique, Asthma Control Test (ACT) score, forced expiratory volume in the first 1 second (FEV1%), and reliever use (puffs/day).Methods: A pre–post interventional study was conducted over 6 months from February 2017 to July 2017 in rural areas in Jordan. Asthma patients visiting respiratory clinics and using metered dose inhaler (MDI) or turbuhaler (TH) controlled medication were randomly recruited. Inhaler technique was assessed via published checklists. The ACT, FEV1%, and reliever use (puffs/day) were assessed. Patients were educated on inhaler technique via demonstration with return demonstration education. All assessments were repeated 3 months post education.Results: A total of 103 (TH, n=44; MDI, n=59) patients were recruited (mean age=46.5±13.5), 74% females. Patients reported an overuse of their reliever (5.1±4.2 puffs/day). Only 2 patients (1.9%) had well-controlled asthma, while the rest had either moderately (19.4%) or poorly (78.6%) controlled asthma. Patients using the MDI achieved 3.03±4.30 ACT score improvement (p<0.001), which is a clinically significant improvement in control. Patients using the TH achieved a statistically significant improvement of 2.07±4.72 (p=0.031). FEV1% improved significantly for MDI users (p=0.005) but not for TH users (p=0.097). Reliever use decreased significantly for MDI and TH users.Conclusion: Asthmatic patients living in rural areas in Jordan reported poor inhaler technique, ACT scores, and FEV1% scores and high use of reliever medications. Pharmacist-led educational intervention resulted in improved inhaler technique scores, ACT scores, and FEV1% scores and lowered reliever use over time.Keywords: inhaler technique, asthma control, reliever use, rural area, pharmacist role